Oridonin supplementation in rabbits may help to improve the outcome of induced atherosclerosis via autophagy induction: Effects of oridonin on atherosclerotic progression. - Sultan, Ahmed; Mohammad, Bassim; Hadi, Najah; Al-Shaibany, Azhar; Philip, Anil; Jamil, Dina; Al-Aubaidy, Hayder (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Inflammation plays a crucial role in the development of atherosclerotic plague. Oridonin is the major active ingredient of the traditional Chinese medicinal herb Rabdosia rubescens. It is a natural terpenoids that is known as a strong anti-inflammatory supplement by acting as a potent inhibitor of the TXNIP/NLRP3 pathway. Hence, it can reduce the severity of inflammation and improve the outcome of atherosclerotic changes. This study aims to evaluate the anti-inflammatory effects of oridonin in the progression of atherosclerotic plague in rabbits. Methods: Sixty-three male rabbits were included. The rabbits were randomly assigned to one of the three study groups (21 rabbits in each group), normal control diet (NC) fed normal diet for 8 weeks, atherogenic control (AC) fed atherogenic diet (2% cholesterol-enriched diet) for 8 weeks, and oridonin treated group (OT) fed atherogenic diet (2% cholesterol-enriched diet) with oridonin (purity 94%, Sigma-Aldrich, USA) at 20 mg/kg orally daily for 8 weeks. After the end of the study, blood and tissue samples were collected for analysis of various markers of inflammation and atherosclerotic plaque progression. Results: Serum lipids showed a statistically significant improvement in terms of reduction in total cholesterol and low-density lipoprotein (LDL) in the OT group compared to the AC group. This was associated with a significant reduction in serum F2-isoprostane (marker of inflammation) and LC3B (marker of tissue autophagy) between the OT group compared to the AC group. There was also a significant reduction in NLRP3 inflammasome RNA expression in OT group, P<0.001. Conclusions: In animal model, with atherogenic diet, oridonin supplementation can significantly improve the outcome of atherosclerosis by its strong anti-inflammatory action.